Comparative chloroplast genomics of series Sakawanum in genus Asarum (Aristolochiaceae) to develop single nucleotide polymorphisms (SNPs) and simple sequence repeat (SSR) markers. Issue 6 (2nd November 2018) - Takahashi, Daiki; Sakaguchi, Shota; Isagi, Yuji; Setoguchi, Hiroaki
ABSTRACT: Series Sakawanum (genus Asarum, Aristolochiaceae) comprises four taxa of forest understory herbaceous plants, which exhibits a geographical cline of calyx lobe length across taxonomic units. To understand the formation process of this series, it is necessary to investigate the evolutionary history based on maternally inherited seed-mediated plastid markers. Using pyrosequencing technique, nearly complete chloroplast genomes of two species ( A. minamitanianum and A. costatum ) were obtained. Furthermore, nine polymorphic chloroplast single nucleotide polymorphisms (SNPs) and 11 simple sequence repeat (SSR) markers were developed. Most of these markers showed interspecific variations and all markers showed transferability to other Asarum species, while most of markers showed little intra-population variations. These chloroplast genomes and markers can be applied in future studies investigating the contributions of the maternal lineage in shaping the population genetic structure of series Sakawanum and the evolutionary processes underlying their morphological diversification including the characteristic calyx lobe length variation. Moreover, this study showed the applicability of comparative chloroplast genome analysis to develop the chloroplast markers for species group for which it is difficult to obtain polymorphism data using the universal primers.